2012
DOI: 10.1590/s0103-84782012005000125
|View full text |Cite
|
Sign up to set email alerts
|

Características morfogênicas do capim-piatã submetido à adubação com efluentes de abatedouro avícola

Abstract: IICaracterísticas morfogênicas do capim-piatã submetido à adubação com efluentes de abatedouro avícola

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
0
5
0
7
Order By: Relevance
“…Basilisk has, on average, 10 to 11 live leaves per tiller, while cv. Xaraés has approximately 3 to 4 live leaves per tiller (Galzerano, Malheiros, Raposo, Morgado, & Ruggieri, 2013), and cvs Marandu, Paiaguás and Piatã possess, on average, 4 to 5 leaves per tiller (Casagrande et al, 2010;Orrico Júnior, Centurion, Sunada, & Vargas Júnior 2013;Germano, Vendruscolo, Daniel, & Dalbianco 2018). Leaf appearance rate (LAR, cm tiller -1 day -1 ), leaf elongation rate (LER, cm tiller -1 day -1 ), stem elongation rate (SER, cm tiller -1 day -1 ), leaf senescence rate (LSR, cm tiller -1 day -1 ), leaf lifespan (LLS, days), final leaf length (FLL, cm), number of live leaves (NLL), herbage mass (HM, kg ha -1 ), leaf mass (LM, kg ha -1 ), stem mass (SM, kg ha -1 ), dead material mass (DMM, kg ha -1 ), undesirable-plant mass (UPM, kg ha -1 ), leaf:stem ratio (L:S).…”
Section: Morphogenetic and Structural Variablesmentioning
confidence: 99%
“…Basilisk has, on average, 10 to 11 live leaves per tiller, while cv. Xaraés has approximately 3 to 4 live leaves per tiller (Galzerano, Malheiros, Raposo, Morgado, & Ruggieri, 2013), and cvs Marandu, Paiaguás and Piatã possess, on average, 4 to 5 leaves per tiller (Casagrande et al, 2010;Orrico Júnior, Centurion, Sunada, & Vargas Júnior 2013;Germano, Vendruscolo, Daniel, & Dalbianco 2018). Leaf appearance rate (LAR, cm tiller -1 day -1 ), leaf elongation rate (LER, cm tiller -1 day -1 ), stem elongation rate (SER, cm tiller -1 day -1 ), leaf senescence rate (LSR, cm tiller -1 day -1 ), leaf lifespan (LLS, days), final leaf length (FLL, cm), number of live leaves (NLL), herbage mass (HM, kg ha -1 ), leaf mass (LM, kg ha -1 ), stem mass (SM, kg ha -1 ), dead material mass (DMM, kg ha -1 ), undesirable-plant mass (UPM, kg ha -1 ), leaf:stem ratio (L:S).…”
Section: Morphogenetic and Structural Variablesmentioning
confidence: 99%
“…Araújo et al (2015) and Carvalho et al (2014) also reported an increase in phyllochron with greater sheath lengths. Plants with lower phyllochron may reach a maximum number of live leaves per tiller faster, allowing more frequent grazing to avoid senescence losses (ORRICO JÚNIOR et al, 2013).…”
Section: Factormentioning
confidence: 99%
“…Isso ocorre devido à forte interação do metabolismo do nitrogênio com o do carbono, uma vez que a fotossíntese fornece direta ou indiretamente a energia necessária para a assimilação de nitrogênio pelas plantas. A resposta real durante a fase linear no aumento de produção de massa seca depende de vários fatores, como o fornecimento de nitrogênio, condições climáticas, disponibilidade de água e suprimento de outros nutrientes (Orrico Junior et al, 2013).…”
Section: Resultsunclassified